Factors associated with knowledge on the spread of HIV/AIDS among Secondary School Students of Groupe Scolaire De Rugando in Kigali City, Rwanda - Mercy Nwankwo, Chinenye; Denyse Sibomana, Uwizeye (IDOSR JOURNAL OF EXPERIMENTAL SCIENCES, 2022)
Human Immunodeficiency Virus has continued to spread in most countries of the world including Rwanda. Youths are particularly vulnerable to HIV/AIDS due to the fact that they are not sufficiently prepared to address problems related to their sexuality and also because they do not have enough real knowledge about HIV and AIDS. The study assessed factors associated with knowledge on spread of Human Immunodeficiency virus (HIV) among students of Groupe Scolaire de Rugando in Kigali city, Rwanda. The study adopted descriptive cross sectional approach among the target population of 950 students in secondary school of Groupe Scolaire de Rugando. About 108 students were randomly selected using the systematic sampling method. Self-administered structured questionnaires were used for data collection for a period of one month with the help of a trained research assistant. The study instrument was pilot tested in mission secondary school outside study population and further validation carried out before it was administered based on consent. The most common predisposing factors in the study to adolescents to HIV/AIDS were curiosity and need to experiment. The study findings, showed that 78% accepted that HIV is transmitted by engaging in unprotected sexual intercourse with an infected person, 65% accepted that risk of contracting HIV is increased by presence of other sex partners, 69% accepted that regular use of condoms helps to reduce the risk of contracting HIV and 55% accepted that by reducing the number of sexual partners, chances of HIV infection are reduced. Additionally, 44 (43.14%, C. I.: 33.37-53.32) of the students indicated that they had previously engaged in sex, while 58 (56.86%, C. I: 46.68-66.63) shows that they did not engaged in sexual practice. Majority of the students who had engaged in sex had never used a condom (59.09%). Usage of condoms were perceived by respondents that it does not allow their partner enjoy sex. This study recommends the need to design interventions that aims to raise awareness on the negative consequences from risky sexual behaviors; increase availability and accessibility of condoms; fight against the entry of drugs in the country as well as their circulation and accessibility to the youth and finally, guidance and counseling services should be introduced in schools.